Applications of Polyester-Based Coatings for Steel Corrosion Protection - Abesach M Motlatle; Suprakas Sinha Ray; Vincent Ojijo; Manfred Scriba (Chemical and Materials Sciences - Developments and Innovations Vol. 1, 2024)
The article is the first inclusive review of the study and the applications of polyester-based coatings for steel corrosion protection. Bio-based polymers and polyesters have the ability to protect metals against corrosion. The impact of corrosion and the challenges encountered thus far are outlined, as well as the solutions encountered in the industry. Secondly, the potential development use of a polyesters-based coating as a promising alternative to current methods such as phosphating, chromating, galvanization, and inhibitors is highlighted. The general use and functionality of the polymer are dictated by the network structure and polyester classes. The review presents novel developments in smart, bio-based, and green chemistry polyester coatings. Lastly, a variety of polyester applications are discussed, including their use in surface coatings and other industrial applications. Untreated steel and mild steel substrates are rarely used for the application of polyester coatings. The corrosion protections of polyester coatings on steel are not reported because of high curing temperatures. Vinyl esters are mostly used for excellent mechanical and adherent properties and resistance to corrosion attacks.